Revitalizing Pure Islamic Study Program: Harmonizing Classical Paradigms with Market Demands in the Era of Disruption - Tedy, Armin; Zikri, M.; Rahmat, Ihsan (Didaktika Religia, 2024)
This article seeks answers by discussing the scholarly paradigm of Islamic study programs in Indonesia, the challenges of era 4.0, and the efforts they are making to survive. Pure Islamic Study program is one that teaches predominantly Islamic texts or is monodisciplinary. The program has been proven to contribute to a skilled and professional workforce, although this is doubtful for the future. The phenomenon of being disinterested, unproductive, and even closed down indicates that pure Islamic study programs are facing serious problems. The research is based on primary and secondary data. Primary data collection comes from observations and interviews. Meanwhile, secondary data was obtained from articles and related policy documents. This article found that the difficulty of pure Islamic study programs to compete is not only caused by market-driven and sophisticated technological developments, but also the conceptual-analytical paradigm originating from the Middle East has been deeply rooted in the learning methods. Islamic study program managers have made efforts by expanding partnership networks, strengthening informal education, and publishing information on social media. This study points to the importance of taking into account the needs of the market and aligning them with the ultimate goal of graduates. Supporting various activities aimed at developing students’ skills beyond those learned in the program is needed.